Single‐cell RNA sequencing profiling in a patient with discordant primary cutaneous B‐cell and T‐cell lymphoma reveals micromilieu‐driven immune skewing. (17th August 2021) - Jonak, C.; Alkon, N.; Rindler, K.; Rojahn, T.B.; Shaw, L.E.; Porkert, S.; Weninger, W.; Trautinger, F.; Stingl, G.; Tschandl, P.; Cerroni, L.; Farlik, M.; et al.
Summary: Background: Primary cutaneous lymphomas comprise a heterogeneous group of B‐cell and T‐cell malignancies which often show an indolent course, but can progress to aggressive disease in a subset of patients. Diagnosis is often delayed owing to clinical and histopathological similarities with benign inflammatory conditions. Especially during early disease, cancer cells are present at relatively low percentages compared with the inflammatory infiltrate, an interplay that is currently only insufficiently understood. Objectives: To improve diagnostics and perform molecular characterization of a complex type of primary cutaneous lymphoma. Methods: Single‐cell RNA sequencing (scRNA‐seq) was performed and combined with T‐cell and B‐cell receptor sequencing. Results: We were able to diagnose a patient with concurrent mycosis fungoides (MF) and primary cutaneous follicle centre lymphoma (PCFCL), appearing in mutually exclusive skin lesions. Profiling of tumour cells and the tissue microenvironment revealed a type‐2 immune skewing in MF, most likely guided by the expanded clone that also harboured upregulation of numerous pro‐oncogenic genes. By contrast, PCFCL lesions exhibited a more type‐1 immune phenotype, consistent with its indolent behaviour. Conclusions: These data not only illustrate the diagnostic potential of scRNA‐seq, but also allow the characterization of specific clonal populations that shape the unique tissue microenvironment in clinically distinct types of lymphoma skin lesions. Abstract : What is already known about this topic? Patients affected by primary cutaneous lymphomas often experience significant diagnostic delay owing to clinical and histopathological similarities with benign inflammatory conditions, especially in early‐stage mycosis fungoides. What does this study add? This study provides a proof of concept that single‐cell RNA sequencing can be applied to diagnose primary cutaneous lymphomas, presenting a complex case of discordant lymphoma as an exemplar. Owing to the existence of two distinct lymphomas within the same organ, we were able to separately demonstrate and compare specific effects of malignant T cells or B cells on the respective tissue microenvironment. What is the translational message? This study demonstrates the feasibility of single‐cell RNA sequencing for the diagnosis and characterization of complex cutaneous lymphomas.